Acute resistance training does not impair cognitive function in Costa Rican older adults - Hernández Gamboa, Rebeca (2019)
Purpose: To determine the acute effect of RT on cognitive performance in healthy Hispanic older adults. Methods: Volunteers were 45 cognitive intact older adults (Mean age = 65.3 ± 3.7 yr.) recruited from a University extension program. Participants were randomly assigned to one of three possible groups (n = 15 in each group): a) High-intensity RT: 3 sets, 8 repetitions at 70% 1-RM, 2-min rest between sets (G1), b) Low-intensity RT: 4 sets, 14 repetitions at 30% 1-RM, 2-min rest between sets (G2), or c) Inactive control (G3). Before and following the experimental intervention, participants completed a comprehensive battery of cognitive tests assessing processing speed, visuospatial processing, executive function and cognitive control, working memory and immediate memory. Following a familiarization phase to RT exercises, participants in G1 and G2 performed 1-RM needed to define the exercise intensity. The intervention session consisted of the cognitive battery tests and five-minute warm-up on a stationary bicycle, followed by the exercise training protocol (knee extension, chest press, knee flexion, seated row, leg press, biceps curl). Immediately after finishing, the cognitive post-test was applied. The control group remained seated on a chair for 30-min and then performed the post-test. A two-way (group x measurement) ANCOVA was carried out using education level as a covariate. Results: Significant improvements were found on visuospatial processing in G1 (Pre = 61.6 ± 2.1 vs. Post = 69.7 ± 2.4 pts.; CI95% = 4.8, 11.4; p ≤ 0.001) and G2 (Pre = 62.4 ± 2.2 vs. Post = 67.0 ± 2.5 pts.; CI95% = 1.2, 8.1; p = 0.009). Processing speed, executive function and cognitive control, working memory and immediate memory were unchanged by acute exercise or rest. Conclusion: Acute RT enhanced or maintained cognitive performance in older adults. Repetitive acute bouts of RT might chronically improve or retard the aging effects on cognitions in older adults.